Photogenerated Aldehydes for Protein Patterns on Hydrogels and Guidance of Cell Behavior. (2nd February 2018) - Ming, Zunzhen; Fan, Jinyan; Bao, Chunyan; Xue, Yuan; Lin, Qiuning; Zhu, Linyong
Abstract: The immobilization of proteins to hydrogels is important and plays a significant role to provide suitable biomimetic material as extracellular matrix for cell behavior mediation. This study describes a novel and universal strategy for photopatterning unmodified proteins on hydrogels. The methodology creates photogenerated aldehyde regions within a protein‐resistant hydrogel and then conjugates unmodified proteins by mild imine ligation with spatial, temporal, and dosage control. The relatively stable aldehyde intermediate enables the facile and highly efficient covalent immobilization of proteins by a postfunctionalization methodology and the sequential protein patterns provide an easy access to control the identity and dynamic change of proteins presented to cells on demand, thus mediating cell behaviors. This approach provides important opportunities for understanding and controlling cell behavior mediated by proteins, and opens up new avenues for hydrogels in tissue engineering and biotechnology applications. Abstract : By a photogenerated aldehyde reaction, proteins can be covalently immobilized on hydrogels without any premodification by a facile postfunctionalization methodology. The control of identity and dynamic changes of proteins mediates cell adhesion, proliferation, and migration on the hydrogel. The successful guidance of cell behavior opens up new avenues for tissue engineering and biotechnology applications of hydrogel biomaterials.